2020
DOI: 10.1177/0018720820970751
|View full text |Cite
|
Sign up to set email alerts
|

External Human–Machine Interfaces Can Be Misleading: An Examination of Trust Development and Misuse in a CAVE-Based Pedestrian Simulation Environment

Abstract: Objective To investigate pedestrians’ misuse of an automated vehicle (AV) equipped with an external human–machine interface (eHMI). Misuse occurs when a pedestrian enters the road because of uncritically following the eHMI’s message. Background Human factors research indicates that automation misuse is a concern. However, there is no consensus regarding misuse of eHMIs. Methods Sixty participants each experienced 50 crossing trials in a Cave Automatic Virtual Environment (CAVE) simulator. The three independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…Authors found an effect of eHMI when the approaching AV was in the 'Gentle Brake' and 'Early Brake' conditions, but no effect of eHMI was shown in the 'Aggressive' braking and 'Constant Speed' conditions. Conversely, in a CAVE-based pedestrian simulator study, Kaleefathullah et al (2020) demonstrated that after a series of exposures to a functioning eHMI conveying a yielding message, approximately 35% of pedestrians walked onto the road when the eHMI was presented but the approaching vehicle was not decelerating. This suggests that pedestrians may become over-reliant on information conveyed through eHMI, to the point where they start to ignore the vehicle movement behaviour.…”
Section: Introductionmentioning
confidence: 97%
“…Authors found an effect of eHMI when the approaching AV was in the 'Gentle Brake' and 'Early Brake' conditions, but no effect of eHMI was shown in the 'Aggressive' braking and 'Constant Speed' conditions. Conversely, in a CAVE-based pedestrian simulator study, Kaleefathullah et al (2020) demonstrated that after a series of exposures to a functioning eHMI conveying a yielding message, approximately 35% of pedestrians walked onto the road when the eHMI was presented but the approaching vehicle was not decelerating. This suggests that pedestrians may become over-reliant on information conveyed through eHMI, to the point where they start to ignore the vehicle movement behaviour.…”
Section: Introductionmentioning
confidence: 97%
“…Focusing on the design of eHMIs for different vehicle types, a study by Lau et al [12] investigated the application of eHMI communication strategies on an automated bus and revealed eHMIs as contribution to a well-working interaction in terms of pedestrians' perceived safety and perceived information quality [12]. However, current research also pointed out negative effects of eHMIs, e.g., overtrust, which can affect the overall safety in urban traffic [13][14][15] and, therefore, need to be investigated for larger vehicle types, e.g., buses, particularly as negative effects here in a pedestrian interaction might lead to serious accidents or even fatalities.…”
Section: Introductionmentioning
confidence: 86%
“…If the vehicle kinematics contradicted the message of the eHMI, pedestrians primarily based their willingness to cross on the vehicle kinematics rather than the eHMI communication (Dey et al, 2020a). In contrast, a study by Kaleefathullah et al (2020) revealed that when the eHMI was on, but the AV did not indicate a braking process, pedestrians still crossed the street. This result demonstrated possible negative effects, i.e., over-trust, which have been also found by other studies (Kitazaki and Daimon, 2018;Holländer et al, 2019;Lee et al, 2021).…”
Section: Joint Role Of Implicit and Explicit Communicationmentioning
confidence: 98%